Improve business ethics and social responsibility of enterprises in the local area Binh Duong province - Bui , Thị Hường (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Business ethics and corporate social responsibility (CSR) are becoming crucial factors in the sustainable development of enterprises in Bình Dương, one of the leading industrial hubs in the country. Effectively implementing business ethics and CSR not only helps businesses achieve stable growth but also enhances their reputation, creates competitive advantages, and contributes positively to the community. This article analyzes the current situation and challenges in improving business ethics and CSR in Binh Dương while proposing specific solutions to encourage businesses to implement them more effectively.